Molybdenum-mediated chemotaxis of Pseudoalteromonas lipolytica enhances biofilm-induced mineralization on low alloy steel surface. (October 2019) - Guo, Zhangwei; Wang, Weiquan; Guo, Na; Zeng, Zhenshun; Liu, Tao; Wang, Xiaoxue
Graphical abstract: Highlights: Mo enhances corrosion protection conferred by P. lipolytica . Mo promotes carbonate precipitation on steel surfaces induced by P. lipolytica . Mo serves as a chemical attractant and increases biofilm formation. Abstract: Formation of biofilm and the subsequent biomineralization on the steel surface are highly influenced by the steel surface properties. Molybdenum (Mo) is a commonly used metal in steel, which can improve its strength and resistance to corrosion. Herein, the effect of Mo on the biomineralization process was investigated by designing low alloy steels containing different concentrations of Mo. Surface characterization showed that moderate concentrations of Mo (such as 0.6 wt%) significantly enhanced the biofilm formation and the mineralization process. Mechanistically, it is demonstrated that Mo ions served as a chemical attractant for Pseudoalteromonas lipolytica and activated the chemotaxis pathway.